A multi-ethnic epigenome-wide association study of leukocyte DNA methylation and blood lipids - Mina-A Jhun (Nature Portfolio, 2021)
Abnormal blood lipid levels are important risk factors for cardiovascular and other various diseases. Here the authors conduct a large-scale multi-ethnic epigenome-wide association study combined with epigenetic (cis-QTL and eQTM) data, and identify CpG-lipid traits associations that are specific to or common across racial/ethnic groups.